LEGAL STATUS OF BUILDINGS AND STRUCTURES BUILT ON THE RIGHT OF CONSTRUCTION - Arakelyan, Narine (State and Law, 2023)
The article covers some issues related to the legal status of buildings and structures built on the right of construction. In particular, the author of the article touched upon the problems associated with legal norms regulating the rights of the developer and the landowner to buildings and structures built on the basis of the right of construction. As a result, the author presented relevant proposals, taking into account the experience of foreign countries to improve these legal norms.
Keywords: the right to build; buildings and structures built on the right of construction; the right to own; use and dispose of superficies; the principle of superficies solo cedit; temporary ownership; pre-emptive right to purchase